2011
DOI: 10.1007/s00382-011-1086-1
|View full text |Cite
|
Sign up to set email alerts
|

Causes of early Holocene desertification in arid central Asia

Abstract: Paleoclimate records of effective moisture (precipitation minus evaporation, or P-E) show a dry (low effective moisture) period in mid-latitude arid/semi-arid central Asia during the early Holocene (11,000-8,000 years ago) relative to the middle and late Holocene, in contrast to evidence for greater-than-present precipitation at the same time in the south and east Asian monsoonal areas. To investigate the spatial differences in climate response over mid-latitude central Asia and monsoonal Asia we conducted a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 40 publications
6
84
1
1
Order By: Relevance
“…Additionally, a composite analysis of sediments from 11 lakes suggested that the moisture condition in the arid central Asia has an inverse phase relationship with that in the Asian monsoon region during the early and late Holocene periods , which covers half a precessional cycle, rather than the in-phase relation illustrated in the current study and also in others. Similar conclusions were also proposed by Feng et al [2011] and Jin et al [2012]. Although, at the present, it is difficult to fully explain why there are discrepancies in regard to the phase relations of moisture conditions between the arid CA and monsoonal EA in different studies, we believe that such discrepancies are at least partly due to the definition of the arid central Asia region.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…Additionally, a composite analysis of sediments from 11 lakes suggested that the moisture condition in the arid central Asia has an inverse phase relationship with that in the Asian monsoon region during the early and late Holocene periods , which covers half a precessional cycle, rather than the in-phase relation illustrated in the current study and also in others. Similar conclusions were also proposed by Feng et al [2011] and Jin et al [2012]. Although, at the present, it is difficult to fully explain why there are discrepancies in regard to the phase relations of moisture conditions between the arid CA and monsoonal EA in different studies, we believe that such discrepancies are at least partly due to the definition of the arid central Asia region.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…Additionally, the heterogeneous terrain and vegetation, as well as the local aerosols, may also play some role on the precipitation changes in the study region. Modeling study [47] suggested that the drought in ACA in early Holocene was caused by weaker and northern displacement of the westerly jet and reduced evaporation in upwind inland lakes (e.g. Caspian Sea) and the North Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 98%
“…Modeling data indicate that the dry climates of central Asia in the early Holocene are not only related to the northward shift of the westerly in the mid-latitudes during winter and spring, but also to the reduced evaporation of the North Atlantic and a series of inland lakes (such as the Caspian Sea) in the upwind regions of the west [41]. In the past millennium, there was a dry climate in the medieval warm period (MWP) and a humid climate during the little ice age (LIA), which were reflected by the records of the westerly regions of China.…”
Section: Arid Region Lakes In Northwestern Chinamentioning
confidence: 99%